EFFECT OF SOME FACTORS ON REACTION DYNAMICS OF THE OFFSHORE STRUCTURE UNDER WAVE - Chung, Nguyem Thai; Chinh, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2014)
The jacket type offshore structures are widely applied for marine states, it has an important role in security, defense and marine economic development. In Vietnam, research and development of marine structures is an urgent task at present. This paper presents finite element algorithm and a calculating method of nonlinear dynamic interaction between jacket type offshore structures and coral foundation under wave and wind loading. The authors have solved the nonlinear dynamic equations by Newmark and Newton-Raphson method and built the calculation program on Matlab software. On the basis of the algorithm and the calculation program has been developed, the authors have investigated the problem with many different parameters to see the influence of these factors: weight, geometry, material to the dynamic response of the marine structures. The results can be applied in calculation, design and construction of the marine structures on the coral foundation under wave and wind loading, contribute to the development of future marine structures.